Ионно-вакуумные приборы для генерации нейтронов в электронной технике - Гулько В. М. Вячеслав Михайлович; Ключников А. А. Александр Александрович; Коломиец Н. Ф. Николай Федорович; Михайлов Л. В. Леонид Викторович; Шиканов А. Е. Александр Евгеньевич (Киев, Тэхника, 1988)
Авт. указаны на обороте тит. л.